2003
DOI: 10.1029/2003jd003736
|View full text |Cite
|
Sign up to set email alerts
|

Phase partitioning and dry deposition of atmospheric nitrogen at the mid‐Atlantic U.S. coast

Abstract: [1] The deposition of atmospheric nitrogen contributes significantly to total nitrogen (TN) entering U.S. coastal water bodies. Nitrogen inputs via wet deposition are well quantified but dry-deposition fluxes are uncertain. In this study, dry fluxes of major atmospheric nitrogen species (including gaseous NH 3 and HNO 3 and particulate NH 4 + , NO 3 À , NO 2 À , and organic nitrogen (ON)) were quantified during a 2-week summer sampling period at Lewes, Delaware, on the mid-Atlantic U.S. coast. Results indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
61
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 56 publications
7
61
1
Order By: Relevance
“…The application of the dynamic resistance model from Sutton et al (1998), which uses nonzero X c (NH 3 ) values and takes into account that deposited NH 3 may (re-)evaporate from surfaces, represents a rather conservative N deposition estimate (lower boundary). Since X c (NH 3 ) was assumed to be zero in several studies (Goulding et al, 1998;Russell et al, 2003;Singh et al, 2001;Tarnay et al, 2001), which implies that NH 3 is persistently net deposited to the surface (see Eq. 1), we have complemented the upper and lower bi-directional flux scenarios by additionally calculating a "deposition only" scenario according to Eq.…”
Section: Resistances Nh 3 Canopy Compensation Point Transferand Depmentioning
confidence: 99%
“…The application of the dynamic resistance model from Sutton et al (1998), which uses nonzero X c (NH 3 ) values and takes into account that deposited NH 3 may (re-)evaporate from surfaces, represents a rather conservative N deposition estimate (lower boundary). Since X c (NH 3 ) was assumed to be zero in several studies (Goulding et al, 1998;Russell et al, 2003;Singh et al, 2001;Tarnay et al, 2001), which implies that NH 3 is persistently net deposited to the surface (see Eq. 1), we have complemented the upper and lower bi-directional flux scenarios by additionally calculating a "deposition only" scenario according to Eq.…”
Section: Resistances Nh 3 Canopy Compensation Point Transferand Depmentioning
confidence: 99%
“…Existing studies do not identify any simple relationship between organic and inorganic nitrogen in the atmosphere which would be anticipated if the organic material had clear and simple anthropogenic sources. For instance, in sites with relatively high concentrations of nitrate from contaminant sources such as the Delaware coast, organic nitrogen concentrations are not exceptionally high (Russell et al, 2003) and Cape et al (2004) in an extensive study at 7 sites in the UK and Neff et al (2002) found no simple relationship to other inorganic nitrogen components. It is therefore not possible to say with any confidence if this organic nitrogen is of predominantly natural or anthropogenic origins.…”
Section: Organic Nitrogenmentioning
confidence: 99%
“…Most studies to date have focussed on organic matter that is either soluble in rainwater or easily extracted by water from aerosols (Cornell et al, 2003) but one study also considered insoluble organic N and noted it to be much more abundant than the soluble organic fraction (Russell et al, 2003). The nature and sources of atmospheric organic nitrogen are largely unknown, and it is undoubtedly composed of a wide range of organic material.…”
Section: Organic Nitrogenmentioning
confidence: 99%
See 2 more Smart Citations